COMPARISON OF CENTROID METHOD AND TREE STANDARD FORMULA FOR ESTIMATION LOG VOLUME - Mohammed Al-allaf (Mesopotamia Journal of Agriculture)
Centroid method with three of the traditional methods used to estimate the volume of logs (Newton`s, Smalien`s, Huber`s) and four species Eucalyptus, Platanus, Cypress and Pine. Different in terms of natural growth had been adopted to determine which of these equations are the best and most accurate in estimating the volume of these species so (30) tree of each species were taken. The measurements taken are the diameter at the breast, height and elevations at various levels began to 0.3, 1.3, 2.3 and up to 6.3 m which represents length of the piece of wood desired in market, and through the use of ordinary models for Newton`s, Smalien`s, Huber`s, Centroid and the real comparing of the volume of the equations and the true volume by using bias, standard error and T-test, we found that equations of comparisons have no-significant effect, but the equation of Newton`s have best estimate for rest of equations in roughly, we recommend using the equation of Newton`s was the best in estimate of volume of the logs of wood.